Neuroimmune Interactions in Pancreatic Cancer - Jun Cheng; Rui Wang; Yonghua Chen (Biomedicines)
Pancreatic ductal adenocarcinoma (PDAC) is a highly aggressive primary malignancy, and recent technological advances in surgery have opened up more possibilities for surgical treatment. Emerging evidence highlights the critical roles of diverse immune and neural components in driving the aggressive behavior of PDAC. Recent studies have demonstrated that neural invasion, neural plasticity, and altered autonomic innervation contribute to pancreatic neuropathy in PDAC patients, while also elucidating the functional architecture of nerves innervating pancreatic draining lymph nodes. Research into the pathogenesis and therapeutic strategies for PDAC, particularly from the perspective of neuroimmune network interactions, represents a cutting-edge area of investigation. This review focuses on neuroimmune interactions, emphasizing the current understanding and future challenges in deciphering the reciprocal relationship between the nervous and immune systems in PDAC. Despite significant progress, key challenges remain, including the precise molecular mechanisms underlying neuroimmune crosstalk, the functional heterogeneity of neural and immune cell populations, and the development of targeted therapies that exploit these interactions. Understanding the molecular events governing pancreatic neuroimmune signaling axes will not only advance our knowledge of PDAC pathophysiology but also provide novel therapeutic targets. Translational efforts to bridge these findings into clinical applications, such as immunomodulatory therapies and neural-targeted interventions, hold promise for improving patient outcomes. This review underscores the need for further research to address unresolved questions and translate these insights into effective therapeutic strategies for PDAC.